PENINGKATAN HASIL BELAJAR MENULIS TEKS LAPORAN HASIL OBSERVASI DENGAN PENDEKATAN INTEGRATIF - Ambarawati, Ni Ketut (Jurnal Pembelajaran Prospektif, 2020)
The aim of this research is to describe the improvement in learning outcomes of writing text of observation report on class X students of SMA Negeri 2 Sungai Raya with an integrative approach. This approach is to increase students' learning motivation so that the learning outcomes obtained are better. This type of research used in this research is classroom action research (CAR) which consists of two cycles. The location of the study was at SMA Negeri 2 Sungai Raya. The research subjects were students of class X IPA2 semester in academic year 2019/2020. The application of the integrative approach is carried out through 5 stages: (a) preparation, (b) problem orientation, (c) group assignment, (d) group presentation, and (e) evaluation. Observations were made using instruments in the form of observation sheets of teacher and student activities to record their activities in learning. Based on Cycle I and Cycle II, the application of integrative approaches in learning Indonesian can be implemented well. It can be seen from the observation sheet of the implementation of research and student activities while following the learning process. The student learning outcomes in writing written text of the observation report has increased, seen from the percentage of learning outcomes that increased from students completeness by 38% in Cycle I to 90% in CycleII. It was proven that the application of the integrative approach can improve student learning outcomes.